Diseño y construcción de un banco de pruebas para obtener las características de motores eléctricos. - Coronel Valdivieso, Enry Manuel (2010)
This thesis work has the fundamental purpose of contributing in the process of teaching-learning of the behavior of the electric motors of alternating current in the students of Electromechanical Engineering of the National University of Loja, the proposed objective is the one of supporting in the technical formation of the students. By virtue of this you had been able to design and to build a bank of tests for the laboratory of Electricity of our career, with which we wait can be carried out the respective ones you practice on electric motors, we also systematize select topics that will be from great help to the moment to understand and to study it. On the other hand we elaborate the guides that allow the respective practices following the development Limits for practical activities of units, laboratory and shops of the career of Engineer Electromechanical, with what we are able to present a clear and concise work that easily will understand each other it. It is exposed the possibility that future students improve this bank of tests and for their guides, for this way to be able to have a good curriculum of studies that I located to the career and our profession among the best.